2022
DOI: 10.1002/pol.20220176
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophilic macroporous monoliths with tunable water uptake capacity fabricated by water‐in‐oil high internal phase emulsion templating

Abstract: In this contribution, a series of well‐defined amphiphilic di‐block copolymers poly(ethylene oxide)‐b‐polystyrene (PEO43‐b‐PSx) with different PS segment lengths of x = 41, 78, and 130 units were synthesized through activators regenerated by electron transfer atom transfer radical polymerization (ARGET ATRP). The as‐prepared block copolymers successfully stabilized the water‐in‐oil (W/O) high internal phase emulsions (HIPEs) containing pH responsive monomers 2‐(dimethylamino)ethyl methacrylate (DMAEMA) and 2‐(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 45 publications
1
5
0
Order By: Relevance
“…A PP12 microreactor is prepared via polymerization of styrene (St) and 2-(dimethylamino)ethyl methacrylate (DEAEMA), with divinyl benzene (DVB), poly(ethylene oxide) 43 -b-polystyrene 64 (PEO 43 -b-PS 64 ), and 2,2'-azobis(2methylpropionitrile) (AIBN) as cross-linker, surfactant, and initiator, respectively (Figure 1d). [12] It is white, and has a disk shape and a typical polymer matrix, with a diameter of 2.5 cm and a thickness of 0.4 cm (Figure 1c). There are abundant tri-coordinated N atoms and OÀ C=O groups in PP12 (Figure 2a).…”
Section: Resultsmentioning
confidence: 99%
“…A PP12 microreactor is prepared via polymerization of styrene (St) and 2-(dimethylamino)ethyl methacrylate (DEAEMA), with divinyl benzene (DVB), poly(ethylene oxide) 43 -b-polystyrene 64 (PEO 43 -b-PS 64 ), and 2,2'-azobis(2methylpropionitrile) (AIBN) as cross-linker, surfactant, and initiator, respectively (Figure 1d). [12] It is white, and has a disk shape and a typical polymer matrix, with a diameter of 2.5 cm and a thickness of 0.4 cm (Figure 1c). There are abundant tri-coordinated N atoms and OÀ C=O groups in PP12 (Figure 2a).…”
Section: Resultsmentioning
confidence: 99%
“…We attribute this to the poor solubility of the block copolymer surfactants in the mobile phase of the SEC instruments, and this result has also been seen in related reports. 47 We first prepared water-in-PDMS emulsions that had an IP volume fraction of 60% and the triblock surfactant or Silube was added at 1 wt % (with respect to the weight of CP). The PDMS-based continuous phase consists of a mixture of pendent-thiol-and vinyl-terminated polysiloxanes.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Alternatively, open-cell pore structures can be obtained by using polymeric surfactants and by initiating the polymerization from the CP. Furthermore, tuning of the pore structure has been achieved using block copolymer surfactants with different ratios of hydrophilic to hydrophobic character. , One method to prepare amphiphilic block copolymer surfactants is reversible addition–fragmentation chain transfer (RAFT) polymerizations, , and this method has been used to prepare surfactants for HIPE stabilization. For example, Debuigne and co-workers synthesized a library of poly­(ethylene oxide)/polystyrene (PEO/PS) block copolymers with different PS contents using RAFT polymerizations to prepare PS/DVB-based polyHIPEs with different degrees of openness. In that work, it was shown that PEO/PS surfactants with equal block ratios obtained the highest degree of openness of ∼10%, and surfactants with the highest PS content obtained the lowest degree of openness of ∼2%.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…ATRP can be adopted to fabricate the polyHIPE platform with functional groups. 53–55 Porous polyHIPEs as the polymerization initiator (inimer) can be decorated with different polymer brushes. PolyHIPEs with a high surface area offer an effective platform for loading β-CD, which could improve the adsorption effect for BPA.…”
Section: Introductionmentioning
confidence: 99%